Does Living With Human Immunodeficiency Virus Increase Pelvic Reconstructive Surgery Perioperative Complication Risk? A Multicenter Retrospective Cohort Study. Issue 7 (July 2020) - Petrikovets, Andre; Weber Lebrun, Emly E.; Carlos, Daniela M.; Perlman, Barry; Florian-Rodriguez, Maria E.; Bochenska, Katarzyna; Eto, Chidimma u; Lespinasse, Pierre; Mahajan, Sangeeta T.; El-Nashar, Sherif; Crisp, Catrina C.; Sheyn, David
Abstract : Objective: To determine if women with human immunodeficiency virus (HIV) undergoing pelvic reconstructive surgery (PRS) have an increased risk of perioperative and postoperative complications compared with HIV-negative controls. Study Design: Multicenter, retrospective matched cohort study of patients with and without HIV infection who underwent PRS between 2006 and 2016. Cases were identified using International Classification of Disease, 9th edition Clinical Modification and 10th edition Clinical Modification and current procedural terminology (CPT) codes encompassing HIV diagnoses and pelvic reconstructive surgeries. Controls were identified as patients without HIV who underwent similar procedures, performed by the same surgeon during the same 1-year period as surgeries performed on patients with HIV. Cases were matched to controls at a ratio of 1:3. The primary outcome was composite complication rate within 1 year of surgery. Results: Sixty-three patients with HIV and 187 controls were identified. There was no difference in the composite complication rate between women with HIV and HIV-negative women (36.5% vs 30.0%, P = 0.15) over 1 year. However, 19.1% of patients with HIV compared with 5.4% controls had Clavien Dindo Grade I complications ( P = 0.002), and 11.1% of HIV patients had urinary retention within 6 weeks of surgery compared with 3.2% of controls ( P = 0.02). After multivariable logistic regression used to adjust for confounders, living with HIV was not associated with an increased risk of complications. Conclusions: Patients living with HIV are not at an increased risk of complications within 1 year of PRS compared with patients without HIV.